2019
DOI: 10.1108/jedt-07-2019-0189
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for health and safety management in Ghana

Abstract: Purpose This paper aims to investigate the contemporary strategies for Health and Safety (H&S) management practices at the construction sites in Ghana. Design/methodology/approach The study used a mixed method approach in conducting a cross-sectional survey at 28 active construction sites in the Kumasi and Accra metropolises of Ghana using questionnaires and interview guide by using purposive, convenience and snowball sampling techniques. Data were collected from 170 survey respondents and 18 interview p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Certainly, regular inspections were required to be undertaken by designated authorities to ensure compliance with the required regulations (Yap and Lee, 2020;Nawi et al, 2016). Simpson and Sam (2019) found that some construction organisations conduct self-auditing and evaluations periodically. Regrettably, inspections and evaluations were not carried out on many construction sites.…”
Section: Approach To Managing the Risk Of Covid-19 On Sitementioning
confidence: 99%
“…Certainly, regular inspections were required to be undertaken by designated authorities to ensure compliance with the required regulations (Yap and Lee, 2020;Nawi et al, 2016). Simpson and Sam (2019) found that some construction organisations conduct self-auditing and evaluations periodically. Regrettably, inspections and evaluations were not carried out on many construction sites.…”
Section: Approach To Managing the Risk Of Covid-19 On Sitementioning
confidence: 99%
“…Therefore, part of the functions of H&S induction training is to introduce new employees to site H&S hazards, practices and regulations. Noting that some workers suffer injuries within the first 30 days on the job (Simpson and Sam, 2019). Hence H&S induction remains one of the measures used to prevent such as incidents.…”
Section: Introduction Hands Induction Training Is a Legal Requirement...mentioning
confidence: 99%
“…For instance, a research which reviewed a total of 164 journal articles published from 1990 to 2017 reveals that 16% of these articles looked at the role of legislation in design for safety implementation [7]. Similarly, the study conducted by Simpson and Sam [8] which aims to investigate the contemporary strategies for Health and Safety (H&S) management practices at the construction sites in Ghana reveals that that most of the construction sites that display improved safety performance adopt either one or a combination of IOP Publishing doi:10.1088/1755-1315/1101/3/032016 2 mandatory OS&H standards. On the other hand, the traditional project parameters in the form of cost, quality, and time are still perceived to be substantially more important than health and safety.…”
Section: Introductionmentioning
confidence: 99%